Membrane-bound model of the ternary complex between factor VIIa/tissue factor and factor X - Melanie P. Muller; Alex Mortenson; Josepha C. Sedzro; Po-Chao Wen; James H. Morrissey; Emad Tajkhorshid (Blood Advances)
Abstract: Formation of the extrinsic complex (EC) on cell surfaces is the event that triggers the coagulation cascade. Tissue factor (TF) and factor VIIa (FVIIa) form the EC together with FX on phosphatidylserine-containing membranes, leading to FX activation by TF:FVIIa. This lipid dependence has made experimental characterization of the EC structure challenging. Using a novel computational methodology combining rigid-body protein-protein docking and extensive nonequilibrium molecular dynamics simulations in the explicit presence of a membrane, we developed, to our knowledge, the first atomic-level model of the EC, taking full account of the role of the membrane. Rigid-body docking generated 1 000 000 protein-only structures that predict the binding of key EC domains. Residue-residue contact information was then used in nonequilibrium simulations to drive the formation of the EC on a phosphatidylserine/phosphatidylcholine membrane surface, providing, to our knowledge, the first membrane-bound model for the EC. Strikingly, in our model, FX makes contact with TF:FVIIa chiefly via its γ-carboxyglutamate–rich (GLA) domain and protease domain, with the majority of the FX light chain (ie, its 2 epidermal growth factor–like domains) out in the solvent, making no direct contact with TF:FVIIa. The TF exosite makes substantial contacts with both the FX- and FVIIa-GLA domains, in which TF residue K165 engages directly with the FVIIa-GLA domain, whereas K166 plays a central role in binding to the FX-GLA domain. These findings underscore the substrate-binding exosite of TF as being pivotal in the formation of the EC, serving as a critical interface linking the GLA domains of both FVIIa and FX.